Assessment of the Effectiveness of the Implemented Operating System And GeologicalTechnical Activities in Oil and Oil-Gas Fields Analysis Methods (The Peerian Journal, 2023)
The effectiveness of the operational system implemented in oil and oil and gas fields and the geological and technical activities carried out is determined by the difference between the actual and the base version of oil production.Methods of calculating technological indicators in the basic version are divided into two main groups: The first group includes descriptions of oil displacement with water and simulation models obtained from multifactorial analysis; The second group includes mathematical models that shed light on the physical nature of the process of oil extraction from different layers. These models are used to a limited extent due to their complexity and inability to fully cover the process of oil field operation in practice.Descriptions of oil displacement with water used in practice can be divided into two types - integral and differential.